IPSAS Adoption in African Countries: Talking or Walking the Talk - Amel Chatti; Salma Dammak Ayadi; Maher Jeriji (Journal of Accounting and Management Information Systems (JAMIS), 2024)
Research Question- How has the diffusion of IPSAS in the African region been influenced by contextual factors, external pressures, and the current status of adoption and implementation across African countries? Motivation- Africa seems to be the region where these standards have been most widely adopted. This region was at the forefront of the adoption of these standards. We have therefore chosen to plot the diffusion curve of these standards, for subsequent analysis. Idea- This paper examines the various phases of the IPSAS dissemination process in developing countries, particularly in the African region. Data- The data are secondary data collected from Studies published by professional accounting bodies such as IFAC and ACCA, as well as publications by international organizations (IMF and World Bank) were also taken into account. Tools- a qualitative method, in line with that conducted by Polzer et al. (2020), based on a literature search using the internet search on "Google" and "Google Scholar". The keywords inserted included "IPSAS and developing countries" and "IPSAS and emerging economies". The references of each resource were used to identify additional resources. Findings- IPSAS adoption in Africa takes many forms, it is indeed a priority for most of these countries. However, the diversity of implementation plans, and the absence of a centralized, coordinated approach, has made monitoring and forecasting progress rather difficult. Contribution- This research contributes to the IPSAS adoption research by examining the dissemination of these norms in African region. This article examines the diffusion and adoption of IPSAS (International Public Sector Accounting Standards) in the African region. We constructed the diffusion curve of these standards to ensure their successful dissemination. Additionally, we conducted an assessment between the announcement of the adoption decision and the actual implementation of these standards.
Keywords: M41; 650; IPSAS adoption; IPSAS diffusion; innovation; public sector; African region